Recent enhancements to the Blocks Database servers. - Henikoff, J G (1997)
The Blocks Database contains multiple alignments of conserved regions in protein families which can be searched by e-mail (blocks@blocks.fhcrc.org) and World Wide Web (http://blocks.fhcrc.org/ ) servers to classify protein and nucleotide sequences. Recent enhancements to the servers include: (i) improved calculation of position-specific scoring matrices from blocks; (ii) availability of the Prints protein fingerprint database for searching in Blocks format; (iii) a representative sequence biased towards the Blocks of a protein family; (iv) a tree constructed from the Blocks of a protein family; (v) links to related World Wide Web pages for a family; and (vi) the new Local Alignment of Multiple Alignments (LAMA) method to search a block against a database of blocks.